Association between hyperuricemia and metabolic syndrome: A cross-sectional study in Tibetan adults on the Tibetan plateau - Yao, Shaoli; Zhou, Yao; Xu, Li; Zhang, Qi; Bao, Shimin; Feng, Huiru; Ge, Weihong (Frontiers in Endocrinology, 2022)
Purpose: This study aimed to assess the relationship of serum uric acid with metabolic syndrome and its components in Tibetan adults on the Tibetan plateau. Methods: A total of 307 participants were enrolled in this study and biochemical parameters including serum uric acid, fasting plasma glucose, white blood cell, lymphocyte count, mononuclear cells, alanine aminotransferase, aspartate aminotransferase, creatinine, and lipid profile were analyzed using standard methods. The IDF criteria were applied to define metabolic syndrome. The association of serum uric acid with metabolic syndrome and its components was evaluated by multivariable logistic regression models. Results: The overall prevalence of metabolic syndrome was 17.3% (53/307) with 19.6% (31/158) in females and 14.8% (22/149) in male participants. The prevalence of hyperuricemia was 40.7% (125/307) with significant differences between the male (53.7%,80/149) and female (28.5%,45/158) groups. In regression analysis, we observed that the risk of MetS was higher in participants in the hyperuricemia group (adjusted OR, 4.01; 95% CI, 2.02~7.99) compared with those in the normouricemia group. After adjusting for all confounding factors, a 9% higher risk of MetS could be shown in participants with SUA increased per 10umol/L (adjusted OR, 1.09; 95% CI, 1.04~1.14). These relationships were not aﬀected by sex or age (p >0.05). After adjusting for the confounding factors, hyperuricemia is positively associated with abdominal obesity (adjusted OR, 2.53; 95% CI, 1.41~4.53), elevated blood pressure (adjusted OR, 2.61; 95% CI, 1.37~4.97), and elevated triglycerides(adjusted OR, 2.47; 95% CI, 1.09~5.57). Conclusions : In our study, hyperuricemia is significantly associated with the prevalence of metabolic syndrome and part of its components, and these relationships are not aﬀected by sex or age. Given the high prevalence of MetS and hyperuricemia among Tibetan adults, more studies are required to explore the role of SUA in the pathogenesis of MetS.